Cumulative live birth rates with autologous oocytes plateau with fewer number of cycles for each year of age > 42 - David B. Seifer; Sarah F. Wang; David Frankfurter (BMC, 2023)
Abstract Objective To disaggregate the Society for Assisted Reproductive Technology Clinic Outcome Reporting System (SART CORS) age category of " > 42" and compare age-stratified cumulative live birth rates (CLBR) > 42 years old. Design Retrospective cohort study of autologous linked ART cycles. Setting United States (US) National ART Database. Patient(s) Women > 42 years old without a history of prior ART cycles who underwent ART between 2014-2020 as reported to the SART CORS database. Intervention(s) Disaggregate the SART CORS age category of " > 42" into age-stratified cumulative live birth rates (CLBR). Main Outcome Measure(s) Age-stratified cumulative live birth rates (CLBR) for women ≥ 43 years old. Results Between 2014-2020, 24,650 women > 42 years old without history of prior ART underwent 58,132 cycles, resulting in 1,982 live births. Women ages 43, 44, 45, 46, 47, 48, 49, ≥ 50 achieved maximal CLBR of 9.7%, 8.6%, 5.0%, 3.6%, 2.5%, 1.5%, 2.7%, 1.3%, respectively. CLBR for women between 43-45 were significantly higher compared to those 46 and older (p < 0.05). Among women 46 and older, CLBR were not significantly different. Women ages 43 and 44 did not exhibit a significant increase in CLBR beyond the 5th cycle. Age 45 and 46 reached CLBR plateau by the 3rd cycle. Age ≥ 47 CLBR plateaued after the first cycle. After adjusting for age, race/ethnicity, BMI, nulliparity, etiology of infertility, number of oocytes retrieved, embryos transferred, blastocyst transfer, use of ICSI, PGT, and ART treatment cycle number, there was no association between markers of ovarian reserve (day 3 FSH and random AMH levels) and live birth for women > 42. Conclusions While CLBR of autologous cycles from women 42 or younger generally plateau by cycle number 5, age-stratified cycles from women > 42 plateau after fewer cycles to maximize CLBR. Patient and physician expectations for maximum CLBR beyond 42 may be practically based on fewer planned cycles before reaching an age-specific CLBR plateau than may have been previously expected.